PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MAHASISWA PGSD UNIVERSITAS SARJANAWIYATA TAMANSISWA MELALUI PROBLEM POSING - Nila Vitasari; Trisniawati Trisniawati (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aims to improve problem-solving skills in Basic Mathematics courses through Problem Posing approach. This research is a Classroom Action Research. The subject of the research is the 2nd semester student of PGSD at Sarjanawiyata Tamansiswa University (UST). The research instruments are observation sheets, pretest and posttest. Data analysis was done by descriptive statistic technique by determining mean, median, mode, lowest score, highest score, and completeness of individual and classical study presented in the percentage form. The result of this research shows that Problem Posing approach can increase the problem solving ability of 2E PGSD students. This can be seen from the increase of the pre cycle stage which shows the problem solving ability of the students which is formerly in 45 % has increase in the first cycle reaching 52,72 % and the second cycle there is also a significant increase of 84 %. This increasing number indicates that the implementation of class action research is successful. According to the result of the research, the implications that can be contributed for the public benefits is this study provides an overview of the student problem solving skills improvement by the time they finish applying the problem posing approach. This learning provides students the opportunity to learn independently and improve their creativity.